2011
DOI: 10.1080/00207144.2011.546263
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis in the Treatment of Morgellons Disease:A Case Study

Abstract: Morgellons Disease is a condition involving painful skin lesions, fibrous growths protruding from the skin, and subcutaneous stinging and burning sensations, along with symptoms of anxiety, depression, fatigue, and memory and attention deficits. The etiological and physiological bases of these symptoms are unclear, making the diagnosis controversial and challenging to treat. There are currently no established treatments for Morgellons Disease. The following case example depicts treatment of a woman with Morgel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…various interpretations about its occurrence, such as the chemtrails, none of which was science-based. On the other hand, the Morgellons' psychogenesis has been only supposed, without clear-cut scientific evidences, by the therapeutic benefits obtained through hypnosis or oral psychoactive drugs, such as pimozide [10][11][12]. Our analyses have revealed that the wires extracted from the patient's skin lesions were the same present in the nose mucus, in the indoor air, and inside the washing machine filter of her apartment.…”
Section: Discussionmentioning
confidence: 75%
“…various interpretations about its occurrence, such as the chemtrails, none of which was science-based. On the other hand, the Morgellons' psychogenesis has been only supposed, without clear-cut scientific evidences, by the therapeutic benefits obtained through hypnosis or oral psychoactive drugs, such as pimozide [10][11][12]. Our analyses have revealed that the wires extracted from the patient's skin lesions were the same present in the nose mucus, in the indoor air, and inside the washing machine filter of her apartment.…”
Section: Discussionmentioning
confidence: 75%
“…These differing results can be explained by methodological factors, such as the hypnotic suggestions used with patients. Studies on other populations, such as patients with haemodialysis, cancer in palliative care or Morgellons disease have reported that hypnosis has a positive effect on anxiety and depression (Gartner et al., ; Plaskota et al., ; Untas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“… 55 , 58 , 60 Only seven of these studies indicated that the subjects had heard of MD. 54 , 56 , 58 , 61 63 , 70…”
Section: Evidence Supporting the Hypothesis Of Dpmentioning
confidence: 99%
“… 55 , 59 , 60 , 66 In contrast, many more case studies indicated that treatment with antipsychotic drugs reduced symptoms but was not curative 55 , 58 , 61 , 66 , 70 , 71 or that antipsychotics were ineffective. 62 , 63 , 65 In fact, Robles et al suggested that treatment with antibiotics was more successful than treatment with antipsychotics, although they too concluded that MD was delusional rather than infectious. They reported that treatment of two patients with doxycycline and no antipsychotics resulted in complete resolution of the condition, while one subject treated with antipsychotics and no antibiotics did not have disease resolution.…”
Section: Evidence Supporting the Hypothesis Of Dpmentioning
confidence: 99%